Morphological cerebral correlates of CERAD test performance in mild cognitive impairment and Alzheimer's disease - Santos, Vasco dos; Thomann, Philipp; Wüstenberg, Torsten; Seidl, Ulrich; Essig, Marco; Schröder, Johannes (Journal of Alzheimer's disease, 2011)
The objective of this study was to investigate the association between structural cerebral changes and neuropsychological deficits in mild cognitive impairment (MCI) and Alzheimer's disease (AD). Sixty patients with MCI, 34 patients with mild to mode
Gesehen am 21.06.2022